Pain at the pump: The effect of gasoline prices on new and used automobile markets - Meghan R. Busse; Christopher Knittel; Florian Zettelmeyer (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2010)
We estimate the effect of gasoline prices on short-run equilibrium prices and sales of new and used cars of different fuel economies. We find that gasoline prices have larger effects on the prices of used cars than of new cars, but that they have large effects on market shares and sales of new cars. We use our findings to estimate a component of the effect of an environmental tax on gasoline, and to investigate whether consumers are myopic about future gasoline costs when they buy cars.
Keywords: 330